Dynamic performance improvement of wind-diesel power system through robust sliding mode control of hybrid energy storage system. Issue 4 (August 2022) - Afzal Thoker, Zahid; Ahmad Lone, Shameem
Off-grid users can be provided with electricity via a hybrid integration of wind power generators and a diesel system functioning as a backup supply. However, due to wind power fluctuations and rapid load changes, system voltage and frequency variances may exceed permitted limits, resulting in aberrant system behavior. Therefore, to improve the dynamic performance of the wind-diesel power system, a hybrid energy storage system (HESS) made of battery and superconducting magnetic energy storage is installed with the system via a converter interface. Based on the switching manifold design, a sliding mode controller with the super-twisting feature is developed over the hybrid energy storage system (HESS) to carry out the required amount of power exchanges with the system accomplished through the control of converter operation. Lyapunov stability analysis is conducted to guarantee the asymptotic stability of the system. MATLAB simulations are performed to validate the improved performance of the system with the proposed scheme.